The Effect of Location Class Category and Pipe Wall Thickness on Risk Level Onshore Pipeline Oil - Zakki Fuadi Emzain; Makhmudul Fikri; Satworo Adiwidodo; Ratna Monasari; Talifatim Machfuroh (Jurnal Polimesin, 2024)
Pipelines are essential infrastructure for efficient oil and gas production operation, necessitating their continuous and reliable functionality in all locations and circumstances. Nevertheless, the pipeline can fail during operation due to multiple detrimental variables. This study evaluated the impact of the location classification category and pipe wall thickness on the risk level of onshore pipelines. The risk assessment method employed was a semiquantitative approach derived from the reference "Pipeline Risk Management Manual" by W. Kent Muhlbauer. The distributing crude oil pipeline, which spans a distance of 18 kilometers and has a diameter of 6 inches, was evaluated. The evaluation yielded a pipeline relative risk score of 0.91, classifying the pipeline as belonging to risk category 1B. Following this, the assessment findings were analyzed for all 36 pipeline segments, classifying 26 segments in the 1B category and the remaining 10 segments in the 2B category. From the analysis results, the difference between the two risk categories was produced by differences in location class categories, where the pipeline segment in location class 1 creates a 1B risk category; meanwhile, class 3 produces a 2B risk category. Furthermore, a pipeline with a wall thickness of 5.156 inches is associated with a risk score of 0.81, but a wall thickness of 4.1 inches yields a score of 1.41. These results indicate that the location class category and pipe wall thickness significantly impact the risk of onshore pipelines.